Evaluation of Adenosine A2A receptor gene polymorphisms as risk factors of methamphetamine use disorder susceptibility and predictors of craving degree. (October 2022) - Wang, Huiying; Ma, Yitian; Wang, Xiaochen; Zhang, Wenpei; Han, Wei; Liu, Haobiao; Li, Miao; Xiao, Jing; Wei, Hang; Wang, Changqing; Sindhwani, Shria; Zhang, Tianxiao; et al.
Highlights: SNP rs5751876 in ADORA2A gene was significantly associated with METH use disorder susceptibility. Strong correlations were identified between serum levels of ADORA2A and the genotypes of SNP rs5751876. The craving degree in patients with METH use disorder was significantly correlated with rs5751876 genotypes. Abstract: The adenosine A2A receptor (ADORA2A) is highly expressed in the central nervous system and plays vital roles in drug addiction. In this study, we aimed to explore the susceptibility of ADORA2A to methamphetamine use disorder (MUD) and the craving degree based on a two-stage association analysis. A total of 3, 542 (1, 216 patients with MUD and 2, 326 controls) and 1, 740 participants (580 patients with MUD and 1, 160 controls) were recruited in discovery and replication stage, respectively. Significant SNPs identified in the discovery stage were genotyped in the replication samples. Serum levels of ADORA2A were measured using enzyme-linked immunosorbent assay kits. The genetic association signal of each SNP was examined using Plink. A linear model was fitted to investigate the relationship between craving scores and genotypes of significant SNPs. SNP rs5751876 was significantly associated with MUD in the discovery samples and this association signal was then further replicated in the replication samples. Significant associations were also identified between serum levels of ADORA2A and the genotypes of rs5751876 ( P  = 0.0002). The craving scores in patients with MUD were strongly correlated with rs5751876 genotypes. Our results suggest that polymorphisms of the ADORA2A gene could affect the susceptibility to MUD and its craving degree.